// End script hiding -->
SOLUTION: rewrite the equation in function form: -x +y = 6
Algebra
->
Functions
-> SOLUTION: rewrite the equation in function form: -x +y = 6
Log On
Ad:
Mathway
solves algebra homework problems with step-by-step help!
Algebra: Functions, Domain, NOT graphing
Section
Solvers
Solvers
Lessons
Lessons
Answers archive
Answers
Click here to see ALL problems on Functions
Question 17301
:
rewrite the equation in function form:
-x +y = 6
Answer by
rapaljer(4670)
(
Show Source
):
You can
put this solution on YOUR website!
Solve for y:
-x + y = 6
Add +x to each side of the equation:
-x+x +y = x+6
y= x+ 6
y = f(x), so
y= f(x) = x+ 6
R^2 at SCC